INDEPENDENT LEARNING - INDEPENDENT CAMPUS INDEPENDENT BUSINESS OF TECHNOLOGY AND COVID-19 VACCINE - Apris Ara Tilome (European Journal of Humanities and Educational Advancements, 2022)
Since the launching of the Independent Learning-Independent Campus (MB-KM) by the government through the Indonesian Ministry of Education and Culture, Research and Technology in Higher Education, it has created a breath of fresh air for higher education to be more advanced in improving the Tri Dharma of Higher Education. Independent Learning Program-Independence Campus, students will have stronger experience, insight, hard skills and soft skills. On the other hand, students can participate in independent projects in conducting applied research with lecturers, and community service. When universities were enjoying the joy of independent learning, the world was shaken by a terrible disaster with the emergence of a deadly epidemic, namely the Covid-19 pandemic or with the term "Corona" throughout the world, including Indonesia. This epidemic has spread both from the economic, political, socio-cultural and religious aspects, even in the education aspect, the impact of COVID-19 which emerged at the end of 2019 in the city of Wuhan (China). The Covid-19 pandemic has made many countries speculate to deal with it in various ways. One of the more effective ways is to generate knowledge of technology to find solutions for how this order of life continues to run normally in general and especially in the world of education, from kindergarten to university levels. In the midst of the Covid-19 pandemic, new technology products have emerged, and even medical scientists have found several types of vaccines to prevent the corona virus. In this paper, the author highlights the technology product business which is again "independent and free vaccine" for an independent life of learning - an independent campus, during the covid-19 pandemic. in relation With the Covid-19 pandemic , the Minister of Education issued circular (SE) No. 3 of 2020 regarding the prevention of the spread and transmission of COVID-19 in educational institutions states that schools and universities are closed. The process of teaching and learning activities (KBM) is carried out at home online. This online learning provides opportunities and opportunities for technology designers to take advantage of the situation by doing business with technology tools or learning applications to support Teaching and Learning Activities (KBM) in the midst of the covid-19 pandemic. Not to mention the findings of several types of vaccines under the pretext of reducing the transmission of covid-19, so that when carrying out face-to-face activities (during) on the condition that lecturers and students must be vaccinated. This Technology and Vaccine Business adorns the world of independent campus education, free to learn during the covid-19 pandemic